THE INFLUENCE OF PRODUCTION FACTORS ON HEMATOLOGICAL AND BIOCHEMICAL BLOOD PARAMETERS IN LABORATORY MICE OF THE JCR LINE, DEPENDING ON THE TYPE AND DURATION OF THEIR EXPOSURE - Савченко, Олег Андреевич; Новиков, Евгений Анатольевич; Новикова, Ирина Игоревна; Чуенко, Наталья Федоровна; Свечкарь, Полина Евгеньевна (Medicine in Kuzbass, 2024)
Preserving the health of the able-bodied population of Russia, establishing the causes and mechanisms of occupational morbidity in order to prevent it in people who are under the influence of physical and chemical factors of the working environment, the severity and intensity of the labor process, for a long time, remains quite an urgent problem. Ethical and technical problems that arise when conducting long-term human studies make it relevant to use outbred nonlinear mice as an accessible experimental model. The study of the features of physiological and pathological reactions potentiated by the influence of physical and chemical factors of the production environment under model conditions (in 90-day experiments on laboratory mice ICR), contributes to the establishment of causes, mechanisms, and approaches to preserving the health of the able-bodied population.The aim of the study was to study the influence of production factors (vibration, noise, a 4–component mixture of chemical aerosols) on hematological and biochemical blood parameters in laboratory mice of the ICR line, depending on the type and duration of their exposure.Material and methods. The study included 130 mice of ICR laboratory mice, divided into 4 groups of 30 individuals (15 females and 15 males) each, in which clinically important hematological and biochemical blood parameters were determined and evaluated in 90-day dynamics with an interval of 1 month, in comparison with the control group.Results and their discussion. In the course of the study, the limits of variability of hematological and biochemical blood parameters in laboratory mice of the ICR line were determined depending on the type of production factors and the duration of their exposure in comparison with the control group.Conclusion. Further study of the influence of production factors on hematological and biochemical blood parameters in laboratory mice of the ICR line, as model organisms, depending on the duration of their exposure, will contribute to the study of mechanisms that contribute to the prevention of the development of pathological processes in the working contingent under the influence of factors of the production environment.
Keywords: production factors; noise; vibration; industrial aerosols; laboratory mice ICR; hematological and biochemical parameters of blood; premature aging